Peran konselor sekolah dalam menangani cyberbullying melalui pembelajaran sosial emosional - Pratiwi, Ratna; Eliasa, Eva Imania (Jurnal Pendidik Indonesia, 2024)
Cyberbullying is a form type of bullying that occurs via digital platforms which includes sending hurtful, insulting or intimidating messages or content intentionally and repeatedly which can have a negative impact on students' emotional well-being and academic achievement. School counselors play an important role in integrating SEL into educational programs to prevent and address cyberbullying. Create positive schools, the aim of this article is to apply Social and Emotional Learning (SEL) in preventive and curative interventions against the negative impacts of cyberbullying.  The method used is descriptive with a systematic literature review (SLR), which analyzes literature related to the application of SEL in reducing the negative impact of cyberbullying. The results showed that cyberbullying had a significant impact on students' emotional and academic well-being, including anxiety, depression, decreased academic achievement and that SEL integration by school counselors helped students develop emotional resilience, improve social relationships, and maintain their academic performance. This research recommends implementing SEL-based anti-cyberbullying policies in schools